Correlation between Lpa, APO-A, APO-B, and Stenosis of Middle Cerebral Artery in Patients with Cerebral Ischemic Stroke. (14th November 2022) - Chen, Xinxu; Lu, Xuefei; Li, Wei; Zhang, Hongyan; Wang, Tan
Abstract : Ischemic stroke (CIS) is characterized by a high incidence, disability, and mortality. Numerous studies have demonstrated that intracranial arterial stenosis is an important pathological basis of CIS, and its main cause is atherosclerosis. Dyslipidemia is an important risk factor for atherosclerosis. Lysophosphatidic acid (Lpa), apolipoprotein -A(APO-A), and apolipoprotein -B(APO-B) proved to be significantly correlated with the severity of coronary artery disease. This study retrospectively collected the case data of 186 patients with CIS treated from May 2020 to May 2022 and explored the correlation between Lpa, APO-A, APO-B, and middle cerebral artery (MCA) stenosis in CIS patients.